Pengaruh Pengembangan Sumber Daya Manusia, Budaya Organisasi Dan Motivasi Terhadap Kinerja Karyawan Pt. Pertamina (Persero) Unit Pengolahan V Balikpapan - Kalimantan Timur - Fariansyah Hassan Basrie, (Bisnis dan Manajemen, 2008)
This research aimed to analyzis effect of 1) human resource development, corporate culture, motivation, toward employee performance, 2) corporate culture toward human resource development, 3) corporate culture toward motivation 4) motivation toward  human resource development,  5) human resource development toward motivation in PT Pertamina (Persero) Proceesing Unit V Balikpapan, East Kalimantan.Furthermore, object of this research was PT Pertamina (Persero) Proceesing Unit V Balikpapan, East Kalimantan. This study using survey method with cross section analyzis. Sample using purposive sampling method. Respondents of this research was 1632 fixed, 1599 unfixed employee of PT Pertamina(Persero) Proceesing Unit V Balikpapan, East Kalimantan. Each of population take as respondents 95 employee, total respondents 190. While returning the questionnaire a number of 174 people (approximately 92%). Model testing using Structural Equation Modelling.In addition, this research found that corporate culture was build with increased innovation culture, organization activity base on employee orientation and take attention to any problem cause by employee bring implication to employee. In the same way, it can give information that interaction and better relation was a side effect of good corporate culture and give space for employee to innovation and it can accommodate existing problem.This research also proving that by developing education and training, working capacity, the ability of knowledge, skill, attitude and on job training, it can reach corporate objective. This research showed that motivation had negative influence toward human resource development.This result also give information, that corporaye culture had not directed effect on work performance. On the other hand, other variable was give spillover effect. It was work motivation. This variable can be organization effort within increasing employee performance and organization